Nutrient Retentivity and Thermal Process Capability of Ohmic-Heated Pasteurizer Compared to Contact-heated Pasteurizer - Jamaludin, Nurul Faezawaty (2008)
Pasteurization of liquid foods using conventional heating is inefficient. The inefficiency as for example the excessive usage of energy, non-uniform and localized heating that contribute to nutrient losses and food poisoning. This study tries to overcome the stated problems by introducing a simple and unique design of an ohmic heating system. The unit consist of the ohmic heating cell and the fluid handling system, and the ohmic heater control panel. The performance of the ohmic heating unit was compared with a plate heat exchanger and evaluated based on three major parameters namely nutrient retentivity; determined by using High Performance Liquid Chromatography (HPLC), destruction of bacteria; based on the plate count method and iron content determination using Atomic Absorption Spectrophotometer (AAS). From this study it was found that the ascorbic acid (vitamin C) in pineapple juice drink degrades by 26.67% in conventional heating and 1.27% in ohmic heating, whereas in pink guava juice it degrades up to 75% and 44% respectively. The time to heat the product to pasteurization temperature is one of the factors in contributing nutrient degradation. In conventional heating especially with heat regeneration, the product heating time is almost 28 minutes compared to 15 seconds in ohmic heating. The destruction of bacteria for both methods gave the same results, which is <10 cfu/ml. The iron content in samples increased significantly in conventional heating up to 70% as compared to ohmic heating 31%. Iron increment in conventional heating method may be due to corrosion on the of process stream whereas in ohmic heating method, the increment is due to electrolytic effect of the electrodes. The performance of the ohmic heated pasteurizer system developed is able to control temperature and meet the pasteurization parameters as set, electrically safe to operate, hygienic in design and lower in cost.